Struktur komunitas laba-laba (Arachnida: Araneae) di Taman Nasional Bogani Nani Wartabone, Sulawesi Utara - Roni Koneri; Saroyo Saroyo (Jurnal Entomologi Indonesia, 2015)
Bogani Nani Wartabone National Park is a tropical low land rain forest. This region has high diversity of arthropods, i.e. spider. The aims of this study was to analyze the Community structure of spiders of spiders (Arachnida: Araneae) in various types of habitat at Bogani Nani Wartabone National Park North Sulawesi. Sampling was carried out at three habitat types, namely primary, secondary, and farm. The research was conducted from March to May 2014 by using pitfall trap (to collect spiders that move on the ground) and sweep net (to collect the spideron vegetation canopy). The number of spiders obtained during the study of was 1267 speciments. The specimens collected are consists 15 families, 71 genera, and 129 morphospecies. The Family which most individual abundance is family Tetragnathidae and the least was Ctenizidae. Salticidae were the most common family of species (30 species), while the least were Agelenidae, Ctenidae and Ctenizidae where each family has one species. Abundance, richness, diversity and evenness of species was higher in the farm, while the lowest in the secondary forest. The highest similarity index of spider communities was between primary forests and secondary forests. The results of this research can be used as a diversity database of spiders for conservation strategies in North Sulawesi.